Ensuring the Development of Sustainable Tourism in the Face of Global Ecological Challenges - Holovnia Olena M. (Bìznes Inform, 2023)
The article is devoted to the problem of theoretical and practical foundations of research and substantiation of mechanisms for the formation and implementation of a strategy for the development of sustainable tourism based on sustainable development of society and harmonization of relationships in the triangle of «ecology – economy – society». The content of the concept of «responsible tourism» is defined, which is considered as tourism that respects the environment, community and culture of a tourist place, is aimed at eliminating the negative consequences caused by irresponsible mass tourism and is oriented toward creating the development of sustainable tourism that protects the interests of local communities and heritage sites in communities. The components of sustainable tourism (geotourism, cultural tourism, ecological tourism) are studied, in which all participants in the tourism process are obliged to protect the natural environment and resources in order to ensure healthy, progressive and sustainable economic growth. It is determined that in the context of the development of sustainable tourism, the role of environmental volunteering and volunteer tourism is growing; the main areas of environmental volunteering are considered as follows: water quality monitoring, wildlife monitoring, animal rehabilitation and rescue, cleaning of plastic garbage. Today, volunteer organizations exist in 80 countries around the world. About 110 million people annually participate in voluntary programs where they lend a helping hand in the fields of education, health, ecology, social protection and many others. The author considers the most famous volunteer tourism programs, including the UNWTO.Volunteers Program, which aims to train young professionals in the tourism industry. The program provides tools for poverty alleviation and development, allowing volunteers to carry out the practical transfer of applied practical know-how, which, in turn, will empower beneficiaries who wish to implement initiatives related to the development of sustainable tourism.